Egypt station [compact disc] - McCartney, Paul; Tedder, Ryan (Capitol, 2018)
Paul McCartney invites listeners on a musical journey with his latest album, which stares a title with one of his paintings. It is the first full album of all new material since his hit 2013 release NEW. Includes the tracks I Don't Know and Come On to Me.